The Role of Youth Schools in Applying Travis Hirschi’s Social Control Theory - Maskuliūnaitė, Radvilė (Acta humanitarica academiae Saulensis, 2025)
The youth school is described as one of the tools that can help to suppress the emerging risks and direct the manifestations of the delinquent behaviour of young people towards the proper purpose and the system of values prevailing in the society. On the other hand, the school can be seen as an authority of control and power, causing hostile reactions and responses to the norms, rules and values that are being introduced. This can encourage young people to become more violent towards social standards, rebel and oppose the prevailing system.The article analyses the impact of youth schools on young people prone to delinquent behaviour according to Travis Hirschi’s social control theory, using the method of the qualitative research – a semi-structured interview. The research raises the following questions: whether youth schools successfully contribute to the socialization of delinquent youth and can give them motivation to return to the traditional education system and the labour market? Or, on the contrary, can they be perceived as institutions that isolate and segregate those who are undesirable and nobody believes in their ability to re-socialize and become full members of the society? In order to answer these questions, interviews with experts-practitioners – specialists working in youth schools were carried out. For qualitative content analysis, empirical data was processed using MAXQDA software tool. By analyzing the results of the research and using the principle of the axial coding, the categories, according to their areas, were split into the first and second level subcategories. The research reveals that the role of the youth school can be assessed in two ways. On the one hand, they can be a successful socializing agent that can help guide young people away from the delinquent behaviour by ensuring socialization, attachment, engagement, commitment and faith. On the other hand, the fact that success is not frequent reveals challenges and difficulties faced by youth schools. Young people do not always take over the values that are introduced at school and start to behave pro-socially, the school is often perceived as a hostile place that does not correspond to the value system of young people. The conclusion can be made that because of the ambivalent evaluation of youth schools, their role cannot be assessed unambiguously.
Keywords: social control theory; youth school; delinquent behaviour; youth